COMMUNICATION STYLES OF GLOBAL BRANDS IN DIFFERENT CULTURAL CONTEXTS: A STUDY OF THE MCDONALD’S BRAND - Scharf, Edson Roberto; Odebrecht da Silva, Halissa (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
The aim of this study is to analyze the communication styles adopted by McDonald’s brand in the North American and Brazilian markets, based on the concepts of Mooij (1998). With qualitative research method, the sample is intentional choice, with the social set consisting of four commercials (two Brazilian and two American) for certain McDonald’s product, resulting in twelve commercials. Through the content analysis technique, the findings showed that the adaptations of communication are similar in both countries. Specifically: a) four Brazilian commercials were classified as direct mode (focused on the individual) and only two Americans are in this mode, contrary to the usual definition about Brazilian people; b) the majority of Brazilian commercials has its verbal communication in the affective type (oriented to the receiver of the message), while the American communication is mostly instrumental (persuasive selling message); c) the possible relationships of similarities or differences regarding the purchasing power did not reveal profound distancies.